La violencia en el seno de las relaciones íntimas, analizadas por un psicólogo clínico - Cacéres Carrasco, José (2022)
This paper reviews data associated with violence within intimate relationships, some of which are frequently reported in the mass communication media, and others which are equally valid, although more subtle, taken from empirical studies and clinical observations. A bio-psycho-social model is presented, with aim of understanding this incoherence. It is argued that, although legal and penal actions might be deemed necessary, they will not succeed unless the “human factor” is taken into account, and the distance that exists between the explicit and implicit demands of those who are implicated, is reduced. Suggestions to implement preventive programmes are put forward.